Minimalist Space: The Influence of Interior Design on the Mental Health of Teenagers - Datinguinoo, Zhyrine Ann Nicole K. (Animo Repository, 2022)
Because mental health is one of the most prevalent health concerns among teens, one of the most influential variables contributing is their personal surroundings. According to research, an interior space design and its design components have the capacity to impact an individual's mental health either favorably or adversely depending on how they are communicated. This research seeks to produce an interior design of a bedroom that embraces a Minimalist idea suitable for improving one's mental health and well-being. A literature study was undertaken to get a better knowledge of the impact of interior design. The review identifies the aspects and characteristics of both a place and its design that may bring to one's self. Using a mixed-method approach, an online survey was given to 50 senior high school students, and an email interview with an interior designer was done to acquire enough credible information on how a design style delivers substantial change to space and to better understand how teens, themselves, feel. As a result of this method, the artwork, Minimalist Space design, was created, which combines the Minimalist concept with biophilic design to build an image or scene with a positive design. This bedroom space design exemplifies how interior design is incorporated into one's lifestyle.